Rosnąca rola mediacji w rozwiązywaniu konfliktów w rodzinie - Karaszewska , Hanna; Rajewska de Mezer , Joanna; Silecka-Marek , Ewelina (Studia Edukacyjne, 2019)
Conflict-related and disputable situations have been present in our lives since ancient times, when people have become aware of the need to protect their rights and interests, sometimes at odds with the aspirations of others. The conflict that emerges between people disturbs their relationships and poses a threat to the proper functioning of people, bringing with them negative emotions. However, it can be an opportunity for development, be treated as a change in interpersonal relationships and can ultimately produce positive effects. Mediation offers a possibility of converting the negative aspects of the conflict into constructive solutions. Being voluntary, confidential, non-formal, out-of-court proceedings, it enables the parties to come to an agreement, offering them the opportunity to actively participate in shaping the legal and social situation and exercising their rights and interests in the spirit of consensus. In the mediation process, the parties use the support of a professional, impartial, neutral mediator. The authors of the article promote the idea of mediation with full conviction that it is a valuable and effective way for conflicted parties and third parties and their relatives to reach a consensus on various issues, including family matters.